Psidium guajava and Piper betle Leaf Extracts Prolong Vase Life of Cut Carnation (Dianthus caryophyllus) Flowers. (29th April 2012) - Rahman, M. M.; Ahmad, S. H.; Lgu, K. S.
Abstract : The effect of leaf extracts of Psidium guajava and Piper betle on prolonging vase life of cut carnation flowers was studied. "Carola" and "Pallas Orange" carnation flowers, at bud stage, were pulsed 24 hours with a floral preservative. Then, flowers were placed in a vase solution containing sprite and a "germicide" (leaf extracts of P. guajava and P. betle, 8-HQC, or a copper coin). Flowers treated with 8-HQC, copper coin, and leaf extracts had longer vase life, larger flower diameter, and higher rate of water uptake compared to control (tap water). The leaf extracts of P. guajava and P. betle showed highest antibacterial and antifungal activities compared to the other treatments. Both showed similar effects on flower quality as the synthetic germicide, 8-HQC. Therefore, these extracts are likely natural germicides to prolong vase life of cut flowers.